miR-26 Induces Apoptosis and Inhibits Autophagy in Non-small Cell Lung Cancer Cells by Suppressing TGF-β1-JNK Signaling Pathway - He, Yi; Liu, Hao; Jiang, Lianyong; Rui, Bi; Mei, Ju; Xiao, Haibo (Frontiers in Pharmacology, 2019)
Non-small cell lung cancer (NSCLC) is one of the leading causes of cancer mortality worldwide. The role of miR-26 in the development and progression of NSCLC remains largely unknown. In this study we found abnormal expression of miR-26 in human NSCLC tissues. It was found that miR-26 mimics induced cell apoptosis and promoted caspase-3, 9 activities in human NSCLC cells. miR-26 inhibitor enhanced the expression of the light chain 3 (LC3) protein and autophagy related genes in NSCLC cells. Moreover, miR-26 regulated apoptosis and autophagy by inhibiting TGF-β expression in a JNK dependent manner. In addition, miR-26 mimics induced cell apoptosis was involved in endoplasmic reticulum stress (ERS) signaling pathway. Down-regulation of ERS inhibited apoptosis induced by miR-26 mimics in NSCLC cells. In in vivo studies, TUNEL staining revealed that the number of TUNEL positive cells of tumor tissue in miR-21 treatment group were significantly increased in comparison with the control group, while the number of TUNEL positive cells of the tumor tissue were remarkably decreased in the groups treated with miR-26 combined with TGF-β1 inhibitor or JNK inhibitor. Additionally, the immunoreactivity of TGF-β1 in cells treated with miR-26 inhibitor decreased in comparison with the control group. Our results indicated that miR-26 induced apoptosis and inhibited autophagy in human NSCLC cells through TGF-β1-JNK signaling pathway, suggesting that miR-26 could be a potential novel target for treatment of NSCLC.